(untitled) (Research, Society and Development, 2020)
The recent oil spill off the Brazilian coast serves as an alert for research to be carried out that includes biotechnological processes and products for cleaning marine environments. Therefore, this work aims to compare the use of residual coconut fibers (Cocos nucifera L.) in natura, pretreated with Protic Ionic Liquid (PIL) [2-HEA] [Ac] (innovative treatment) and by mercerization/acetylation (traditional treatment) as a biosorbent of petroleum spilled in the marine environment in a hydrodynamic simulation on a laboratory scale. The study of the kinetics and adsorption equilibrium were performed to determine the limiting mechanism of adsorption, as well as the maximum petroleum adsorption capacity for the coconut fibers studied. Characterizations of the fibers were carried out using SEM and FITR, and the kinetics and sorption equilibrium tests with petroleum from the Campos Basin and saline water. It was possible to observe that a minimum time of 5 min of contact between the adsorbent and adsorbent is necessary for biosorption to occur. The fibers treated with PIL (4.63 g/g) had greater sorption capacity, the fiber in natura (3.62 g/g) less capacity and the fiber with mercerization/acetylation treatment (4.26 g/g) has sorption with intermediate values. The kinetic model that best fitted the experimental data was pseudo-second order, indicating chemosorption as the limiting step of adsorption. The sorption equilibrium model chosen was Sips, determining adsorption in multilayer (Freundlich) with low concentrations of petroleum and in monolayer (Langmuir) with high concentrations. Based on these results, it can be said that the coconut fibers (Cocos nucifera L.) treated have a greater capacity to adsorb petroleum than the fibers in natura, and the fibers treated with PIL [2-HEA][Ac] have greater sorption capacity, among those evaluated, to be used in oil spills.